2020
DOI: 10.1021/acs.jpcc.0c03465
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Donor Solvents Strongly Coordinate Pb2+ in Hybrid Organic–Inorganic Perovskite Precursor Solutions

Abstract: Strong coordination between Lewis-basic processing additives and the Lewis-acidic lead halide in hybrid organic− inorganic perovskite (HOIP) precursor solutions is required to solubilize the lead halide, and subsequently access the appropriate crystallization kinetics and attain the desired morphology of perovskite active layers. While oxygen-donor solvents and additives, such as dimethylformamide and dimethyl sulfoxide, are widely used for perovskite processing, we demonstrate that "soft" sulfur-donor solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 49 publications
5
56
0
Order By: Relevance
“…However, several studies have shown that the defect state density of polycrystalline perovskite films is several orders of magnitude higher than that of single-crystal perovskite films. This is primarily because of unavoidable structural defects such as uncoordinated Pb 2+ at the surface of the polycrystalline perovskite film [ 61 , 62 ]. These defect sites not only capture photogenerated carriers and cause energy loss, they also easily adsorb substances such as moisture and oxygen in the environment, thereby accelerating the degradation of the perovskite film.…”
Section: Psc Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have shown that the defect state density of polycrystalline perovskite films is several orders of magnitude higher than that of single-crystal perovskite films. This is primarily because of unavoidable structural defects such as uncoordinated Pb 2+ at the surface of the polycrystalline perovskite film [ 61 , 62 ]. These defect sites not only capture photogenerated carriers and cause energy loss, they also easily adsorb substances such as moisture and oxygen in the environment, thereby accelerating the degradation of the perovskite film.…”
Section: Psc Interfacementioning
confidence: 99%
“…Many passivation molecules directly neutralize the surface charges or dangling bonds to annihilate the corresponding electron traps [ 98 , 99 , 100 ], e.g., by introducing Lewis bases (such as thiourea) to coordinate with Pb 2+ on the surface and grain boundaries to reduce the defect density; some electron trap states can accept one of the Lewis-based defects on the surface of the perovskite through the Lewis acid molecule electron to be reduced [ 62 , 101 , 102 , 103 , 104 ]. The molecular hydrophilic chemical group and perovskite molecule combine to form a coordination bond, which is conducive to the transport of carriers [ 60 , 105 , 106 ].…”
Section: Interface Modificationmentioning
confidence: 99%
“…On the other hand, NMPT is a “softer” sulfur‐donor solvent also known to coordinate strongly with Pb 2+ . [ 24 ] We have observed that NMPT as an additive provides morphological control of MHP films and is stable against reactions with methylammonium. We hypothesized that the introduction of A‐site impurities (i.e., DMA + and NH 4 + ) resulting from the reactions of MA + and DMSO could lead to trap states in the fully‐formed perovskite film.…”
Section: Figurementioning
confidence: 99%
“…trend is in agreement with the relative formation energies of the Pb 2+ (solv) n complexes, evaluated for n = 1–7 and solv = DMSO, DMF, GBL, ACN, and H 2 O as per eq 2 , see Table 3 . Following the work of Hamill et al, 89 we also consider the relative formation energy for the PbI 2 (solv) n adducts with n = 1 as a supplementary indicator, c.f. Table 3 , the observed trend being consistent with that provided by the energetics of Pb 2+ –solvent interactions.…”
Section: Resultsmentioning
confidence: 99%